Cyclitol based metal complexing agents. preference for the extraction of lithium by myo-inositol based crown-4-ethers depends on the relative orientation of crown ether oxygen atoms - Dixit, Shailesh S.; Shashidhar, M. S.; Devaraj, Subramanian (Tetrahedron, 2006)
myo-Inositol derived crown-4-ethers in which two of the oxygen atoms in the crown ether moiety have different relative orientations were prepared. Metal picrate binding studies revealed that the crown ether having 1,3-diaxial orientation shows the highest selectivity for binding to lithium although the crown ether having 1,2-diequatorial orientation exhibited the highest binding constant for lithium picrate. These results suggest that relative binding affinity of metal ions to crown ethers can be tuned by varying the relative orientation of crown ether oxygen atoms. The relevance of these results to the previously observed regioselectivity during the O-substitution of myo-inositol orthoesters is discussed. (c) 2606 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; lithium; metal complex

Inositol derived crown ethers: effect of auxiliary protecting groups and the relative orientation of crown ether oxygen atoms on their metal ion binding ability - Dixit, Shailesh S.; Shashidhar, Mysore S. (Tetrahedron, 2008)
The binding constants of crown ethers prepared from tetra-O-substituted myo- and scyllo-inositol derivatives and 2-O-substituted myo- and scyllo-inositol-1,3,5-orthoformates, with metal picrates show that the O-substituents and the relative orientation of the crown ether oxygen atoms contribute significantly to the binding of crown ethers with metal ions. In particular, the binding efficiency of myo-inositol derived crown ethers to silver and potassium ions could be enhanced by introducing benzyl ethers in the inositol ring. Hence binding efficacy and selectivity of metal ions to inositol derived crown ethers can be tuned by varying substituents on the myo-inositol ring and/or the relative orientation of crown ether oxygen atoms. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: crown ether; Cyclitol; Inositol; ligand; metal complex; supramolecule

Morphological study of heavy metal complexes of chitosan and crosslinked chitosans by SEM and WAXRD - Trimukhe, K. D.; Varma, Anjanikumar (Carbohydrate Polymers, 2008)
Metal complexes of salts of Hg, Cu, Cd, Pb, Zn, and Mn with chitosan and crosslinked chitosans were prepared, and their morphologies were studied using scanning electron microscopy and wide angle X-ray diffraction. The metal ions which were specifically and strongly complexed to the amino functions of chitosans, like Hg, showed smooth surface morphology inspite of large number of ions complexed (372 mg/g of chitosan). The presence of metal ions on the surface of the chitosans could be detected with decrease in metal ion binding, in the following sequence Hg > Cu > Cd > Zn > Pb > Mn. Particularly in the case of Pb ions, the presence of these ions is clearly seen on the surface of the polymer by SEM. The number of ions of Mn complexed on the polymers was too few (5 mg/g of chitosan) to be visible. SEM of Hg and Cu complexes do not show the ``holes'' observed in the crosslinked polymers as they bind specifically to amino groups of chitosan, but for Cd, Zn, Mn, and Pb complexes, these ``holes'' are clearly visible. These results are also in agreement with the morphologies studied by WAXRD. The metal complexation data for each of these metal ions was also in the same sequence. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Crosslinked chitosan; metal complex; Morphology; SEM; WAXRD